Predicciones de precipitación y temperatura del modelo climático global HadCM3 para la cuenca hidrográfica del río Portoviejo - Moreira Santana, Gualberto Abad (2015)
The aim of this study was to establish the rainfall and temperature of global climate model HadCM3 from the fourth report of the intergovernmental panel on climate change (IPCC) for the Portoviejo River watershed. For this monthly anomalies of weather variables were used the HadCM3 British model, in emissions scenarios A1B, B1 and B2 were obtained. Following this simulation of future precipitation and temperature predictions for short (2010-2039), medium (2040-2069) and long term (2070-2099) using the historical record observed during the period 1964-2012. The results were 9 predictions of precipitation and 9 temperature forecasts, which enabled them to identify anticipated changes in the Portoviejo River basin in the context of climate change. Determining a decrease in precipitation variable in the period 2010-2039 for A1B (up -10,59 mm) and A2 (up -33,89 mm) scenarios, and a gradual increase in temperature in the A1B, A2 and B1 scenarios in the three periods analyzed. Having a short-term increase of up 1,41 ºC medium term of 1 °C to 3 °C and long-term to about 5 °C.